Digital Self-Enslavement: The Implications of the Internet of Things for Cyber Law Reform in the Society 5.0 Era within the Framework of Maqashid al-Sharia - Lbn Batu, Dewi Pika; Siahaan, Parlaungan Gabriel; Taufiq Ramadhan; Pinem, Windawati; Maulana Ibrahim; Sitorus, Gita Oktaviani (Al-'Adl, 2026)
This study investigates the emerging phenomenon of "digital self-slavery" (perbudakan diri digital) within Indonesia's Society 5.0 landscape, focusing on the TikTok live-streaming ecosystem as a site of voluntary self-exploitation mediated by algorithmic systems. Employing a mixed-method approach combining an online survey of 304 respondents with qualitative essay analysis and social media observation this research identifies a critical gap in existing digital slavery literature, which predominantly addresses externally coerced exploitation while neglecting voluntary self-exploitation through digital platforms. Drawing on the Modern Slavery Wheel theory, the digital labor exploitation framework, and the Islamic jurisprudential concept of maqashid al-syariah, this article introduces "self-slavery" as a distinct analytical category separating it from conventional modern slavery. Empirical findings reveal that 85.5% of respondents—predominantly Generation Z—classified online gift-begging behavior as technology-disguised slavery, directly refuting the prevailing social stigma of generational digital apathy. Additionally, 33.2% reported experiencing algorithmic pressure to follow social media trends, and 73.3% expressed support for cyber law reform. From the Islamic legal perspective, this practice constitutes violations of hifzh al-'irdh (preservation of honor) and hifzh al-nafs (preservation of the self), rendering it inconsistent with the objectives of Islamic law. The study concludes that Indonesia's current cyber law framework—including the ITE Law and Presidential Regulation No. 47 of 2023—is structurally insufficient to address nuanced forms of digital self-exploitation, and proposes a reform agenda grounded in both positive law and Islamic normative principles.